PENENTUAN KANDUNGAN ANTIOKSIDAN DAN FENOLIK TOTAL DARI EKSTRAK TUMBUHAN SEBAGAI BIOREDUKTOR DALAM PEMBENTUKAN NANOPARTIKEL PERAK - Dini Hanifa; Refilda Refilda; Akmal Djamaan (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2023)
The formation of metal nanoparticles (silver, gold, platinum) by biological methods (green synthesis) has advantages over chemical and physical methods because it is easier, faster, simpler, and environmentally friendly. One of the substances used in this method is plant extracts. The presence of secondary metabolites that act as antioxidants such as phenolics and flavonoids play roles in the formation of silver nanoparticles. In this study, phytochemical screening was carried out from several herbal plants as bioreductors in the formation of silver nanoparticles, such as Phyllanthus buxifolius, Pachira aquatica, Peperomia pellucida, Ageratum conyzoides, and Piper crocatum leaf extracts. The total antioxidant content was determined using the modified phenanthroline method, and the total phenolic content determined using the Folin-Ciocalteu method. The formation of silver nanoparticles was carried out by mixing silver nitrate solution with each plant extract. Colloidal silver nanoparticles formed were then measured for their absorption spectra. The results of the antioxidant content of the five consecutive samples were 26,90 ± 0,19; 26,09 ± 0,14; 18,25 ± 0,02; 42,76 ± 0,14; dan 30,94 ± 0,14 mg AA/g, while the total phenolic contents were 48,44 ± 0,45; 21,08 ± 0,92; 17,42 ± 0,27; 57,71 ± 0,47; dan 49,83 ± 0,60 mg GA/g. Silver nanoparticles mediated by Ageratum conyzoides leaf extracts provided the highest absorbance value compared to other plants. The antioxidants and phenolic contained in the extract acts as reducing agent from silver ions into silver nanoparticles.